Remedial after-school support classes offered in rural Gambia (The SCORE trial): study protocol for a cluster randomized controlled trial. Issue 1 (December 2015) - Boone, Peter; Camara, Alpha; Eble, Alex; Elbourne, Diana; Fernandes, Samory; Frost, Chris; Jayanty, Chitra; Lenin, Maitri; Silva, Ana
Abstract Background Low education levels are endemic in much of the developing world, particularly in rural areas where traditional government-provided public services often have difficulty reaching beneficiaries. Providing trained para-teachers to teach regular after-school remedial education classes has been shown to improve literacy and numeracy in children of primary school age residing in such areas in India. This trial investigates whether such an intervention can also be effective in a West African setting with similarly low learning levels and difficult geographic access. Methods/Design Design: cluster-randomized controlled trial. Clusters: villages or groups of villages with 15–300 households and at least 15 eligible children in the Lower River and North Bank Regions of The Gambia. Participants: children born between 1 September 2007 and 31 August 2009 planning to enter the first grade, for the first time, in the 2015–2016 school year in eligible villages. We anticipate enrolling approximately 150 clusters of villages with approximately 6000 children as participants. Intervention: a program providing remedial after-school lessons, focusing on literacy and numeracy, 5 to 6 days a week for 3 years to eligible children, based on the intervention evaluated in the Support To Rural India's Public Education System (STRIPES) trial (PLoS ONE 8(7):e65775). Control: both the intervention and control groups will receive small bundles of useful materials during annual data collection as recompense for their time. If the education intervention is shown to be cost-effective at raising learning levels, it is expected that the control group villages will receive the intervention for several years after the trial results are available. Outcomes: the primary outcome of the trial is a composite mathematics and language test score. Secondary outcomes include school attendance, enrollment, performance on nationally administered exams, parents' spending on education, spillover learning to siblings and family members, and school-related time use of parents and children. Subgroup analyses of the primary outcome will also be carried out based on ethnic group, gender, distance from the main highway, parents' education level, and school type. The trial will run by independent research and implementation teams and supervised by a Trial Steering Committee. Discussion Along with the overall impact of the intervention, we will conduct a cost-effectiveness analysis. There are no major ethical issues for this study. Trial registration Current controlled trialsISRCTN12500245 . 1 May 2015.